Soil quality and microbial diversity in relation to the severity of coffee leaf rust disease in Karnataka, India - Poojashree Nagappa Kummur; Devarajan Thangadurai; Jeyabalan Sangeetha; Simran Panigatti; Ravichandra Hospet; Smita Shinde; Guggalada Govardhana Yadav; Kondenahalli Narayanaswami Vijaykumar; Umesh Madar; Kasem Soytong; Jiaojiao Song (Universitas Sebelas Maret, 2025)
Soil physico-chemical properties significantly influence the quality, growth, productivity, and flavor of coffee. The current study estimates the soil nutritional properties and microbial diversity with the severity of coffee leaf rust disease. A total of twenty-nine localities were surveyed in the major coffee-growing district of Karnataka, mainly Chikkamagaluru, Kodagu, and Hassan, covering the canopies of arabica and robusta coffee plantations. The study on soil quality evaluation determines the sustainability and practices of land management in this region. The physico-chemical properties and microbial diversity of the soil were analysed. Twenty-nine soil parameters were analyzed using principal component analysis, which accounts for five principal components with eigenvalues>1 explaining 9 % of the total variance. The nine principal components together explain 82.24 % of the total variance. According to K-means clustering, soil analysis can be classified into four clusters. Soil microbial communities primarily control the complex ecosystems of soil, including root- and rhizosphere-associated beneficial microbes, and play a vital role as key components in crop production and sustainable agriculture. The present study revealed that the fertility level of the soil and the diverse taxa of rhizospheric microflora from various soil samples, characterized by an abundant diversity of beneficial microbes, such as Trichoderma sp., Bacillus sp., Penicillium sp., and Pseudomonas sp. Furthermore, this work gives insights into the sustainable soil quality and disease management practices that can help farmers to adopt better soil management practices for improving the quality and quantity of coffee production in Karnataka, India.